The immunological response among COVID-19 patients with acute respiratory distress syndrome - Abdulaziz S. Almutairi; Hassan Abunurah; Abdulkarim Hadi Alanazi; Faraj Alenazi; Hassan Nag; Nafea Saad Almutairi; Michael Wells; Abdullah Alawam; Mohammed M. Alqahtani (Elsevier, 2021)
Coronavirus disease 2019 (COVID-19) often results in pneumonia and can lead to acute respiratory distress syndrome (ARDS). ARDS is one of the most significant causes of death in patients with COVID-19. The development of a "cytokine storm" in patients with COVID-19 causes progression to ARDS. In this scoping review, we investigated the effect of pro-inflammatory cytokines in inducing moderate and severe ARDS outcomes. A comprehensive search was performed using PubMed and Google Scholar to implement a broad query that captured all the relevant studies published between December 2019 and September 2020.We identified seven studies that evaluated the immune response in COVID-19 patients with ARDS. The white blood cell counts (WBCs), CRP, and IL-6 were higher in the moderately presenting ARDS patients, critically ill patients, and those with more severe ARDS. This study may contribute to better patient management and outcomes if tailored immune marker interventions are implemented in the near future.